Effects of animated pedagogical agent-guided loving-kindness meditation on flight attendants’ spirituality, mindfulness, subjective wellbeing, and social presence - Liu, Chao; Chen, Hao; Zhou, Fang; Chiang, Chao-Hung; Chen, Yi-Lang; Wu, Kan; Huang, Ding-Hau; Liu, Chia-Yih; Chiou, Wen-Ko (Frontiers in Psychology, 2022)
Loving-kindness meditation was first practiced by buddhists and then developed by clinical psychologist, previous studies on loving-kindness meditation have mainly focused on the impact of real person guided meditation on depression, anxiety and other negative psychology. In times of epidemics, this study explored the effect and mechanism of media-guided loving-kindness meditation on the improvement of social pres-ence, subjective well-being (SWB), mindfulness, and spirituality from positive psychology’s viewpoint and compared the different media effects of animation guided loving-kindness meditation and audio guided loving-kindness meditation on mindfulness, spirituality, and SWB. A total of 82 flight attendants were re-cruited from Airlines, We then randomly assigned participants to either animation intervention group (41 participants) or the audio meditation intervention group (41 participants), which both underwent an 8-week LKM training intervention. The aforementioned four main variables were measured before and after the meditation experiment. The results indicated that both audio guided meditation and animated guided med-itation significantly improved subjects' spirituality and subjective well-being. Compared with audio guided meditation, animated guided meditation significantly improved the subjects' spirituality, subjective well-being, and social presence. Audio guided meditation has no significant effect on social presence. This study highlights animation guided meditation has a positive effect on spirituality and SWB, which may provide individuals with a simple and easy method to improve their happiness.